SELF-ACCEPTANCE AND SELF-CONCEPT AMONG TRANSGENDER IN INDONESIA - Reni Fitriani; Agni Laili Perdani; Lia Juniarni (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Transgender is no longer classify a mental health illness from World Health Organization (WHO). The number of this community up to 3.9 million or 1.6% from Indonesia citizen. Transgender face social discrimination and stigma toward themselves as a result from community and family rejection. This condition could affected their process of self-acceptance and self-concept.Purpose: This study aimed to describe the self-acceptance and the self-concept among transgender in Indonesia    Methods: A cross-sectional study was conducted in transgender community at Srikandi Pamungkas, Lembang. This study used a convinience sampling and 30 respondents agreed to participate. Data was collected using self-questionnaire and consist of 52 item questions with.Results: This study showed that the total of transgender with good self-acceptance is 17 (56.7%) and good self-concept is 16 (53.3%)Conclusion: Most of the transgender in the transgender community had good self-acceptance and good self-concept from the support system in community environment.